Effects of A High-Person-Centered Response to Commenters Who Disagree on Readers' Positive Attitudes toward A News Outlet's Facebook Page. Issue 3 (12th April 2022) - Masullo, Gina M.; Ziegele, Marc; Riedl, Martin J.; Jost, Pablo; Naab, Teresa K.
Abstract: This study examined what type of response to commenters who disagree led to more positive attitudes toward a news organization's Facebook page. Results of two experiments, one in Germany ( n  = 764) and one in the United States ( n  = 763), found that a high-person-centered (HPC) response, which acknowledges people's emotions, led to more positive attitudes toward the news organization's Facebook page, compared with a low-person-centered (LPC) response, which dismisses people's feelings. This held true for both German and American participants, regardless of whether the comments were civil or not. In both countries, positive evaluations of the organization's Facebook page were heightened if journalists, rather than news users, responded to the commenters. Results are discussed in relation to the verbal person-centered (VPC) theory of social supportive outcomes.